Investigating The Effect of Machining Parameter on Milling Product Surface Quality Using Doe Approach - Muhammad Yusuf; Teuku Hafli (Faculty of Engineering, Malikussaleh University, 2018)
Machining process is one of the complex processes which have numerous factors contributing towards the quality of the finished product. Milling process is one among the machining process in which quality of the finished product depends on the tool geometry, accuracy of machine tool and cutting condition. The research was done to investigate the effect of machining parameters on product surface quality in milling process. The experiments conducted on a conventional milling machine use of cutting fluid. Material AISI 1050 and HSS end mill cutting tool used for the experiments. Three cutting parameters such as spindle speed, feed rate and depth of cut at two-level was planned using design of experiment (DoE) methodology. The result show that the better surface quality of milling process is obtained for the minimum value of surface roughness (Ra = 1.481 μm). The Analysis of Variance inferred that the spindle speed cutting parameter has significant effect on the surface roughness (Ra).